Regulatory B Cells Are Decreased and Impaired in Their Function in Peripheral Maternal Blood in Pre-term Birth - Busse, Mandy; Campe, Kim-Norina Jutta; Redlich, Anke; Oettel, Anika; Hartig, Roland; Costa, Serban-Dan; Zenclussen, Ana Claudia (Frontiers in Immunology, 2020)
Preterm birth (PTB) is defined as birth before 37 completed weeks of gestation. The causes of PTB are multiple and complex, being the underlying pathophysiology largely unknown. Interferences in the fine-tuned balance of the maternal immune system have been pointed as one possible cause of PTB. Regulatory B cells (Breg) are part of the adaptive immune response and recent data suggest that they may contribute to a healthy pregnancy by their regulatory/ suppressive function. We investigated the frequency of Breg cells in peripheral blood of women undergoing PTB and control women immediately before giving birth via cesarean section. We detected an enhanced number of B cells, but a reduced number of Breg cells in women delivering preterm. In addition, the percentage of IL-10 producing B cells was decreased in PTB following stimulation with TLR agonists CpG or LPS, alone or combined with CD40L. This was associated with increased levels of pro-inflammatory cytokines in maternal serum. Moreover, isolated maternal B cells before delivering premature babies secreted higher level of the pro-inflammatory cytokine IL-6. No alterations in the frequency of regulatory T cells were found. Our data indicate that alterations in the number and function of Breg cells in peripheral maternal blood contribute to the immunological changes observed in preterm delivery and suggest these cells as important regulators of maternal immune responses.